Porous medium 3D flow simulation of contrast media washout in cardiac MRI reflects myocardial injury - Riazy, Leili; Schaeffter, Tobias; Olbrich, Marc; Schueler, Johannes; Knobelsdorff‐Brenkenhoff, Florian; Niendorf, Thoralf; Schulz‐Menger, Jeanette (Magnetic resonance in medicine, 2019)
Purpose Myocardial blood–flow simulation based on laws of fluid mechanics is a valuable tool for understanding tissue behavior. Our aim is to evaluate the ability of a porous‐media flow model approach to reflect disturbed washout of contrast media (CM) from the myocardium as observed by cardiovascular MR. Methods A coupled advection‐diffusion model is used to describe the CM flow in the vascular and extravascular space as separate compartments. Their exchange of CM is controlled by the exchange rate ExR, which in turn determines the washout behavior. We fitted simulations to CM concentration measurements, derived from T1 maps of the midventricular slice. The CM concentration was extracted from 18 patients with myocarditis in the acute phase and during follow‐up after 6 months. The results were compared with 18 sex‐ and age‐matched controls. For each subject, the measurements were acquired before and during the first 10 minutes at 5 time points after CM administration, representing CM washout. Image registration was applied to compensate for motion between different time points. Results Eight matched data sets had to be excluded due to low registration quality. Processing was successful in n = 10 matched data sets of acute and healed myocarditis as well as controls. Significant differences in ExR were observed when comparing patients with acute myocarditis to controls (P < .001), to their follow‐up (P < .05), and the follow‐up to controls (P < .05). Conclusion Our study suggests the feasibility of using the proposed porous‐medium flow framework for the simulation of pathologic myocardial tissue.